VIRTUE AND HIERARCHY IN EARLY CONFUCIAN ETHICS. Issue 4 (1st February 2022) - Yin, Peng
Abstract: Aaron Stalnaker's Mastery, Dependency, and the Ethics of Authority proposes a moral vision that reclaims authority and dependency as indispensable conditions for fostering autonomy. Contemporary Western ethics, argues Stalnaker, is mired in faulty thinking about a set of linked concepts that inhibits an appreciation for the ubiquitous fact of human interdependence. The nature of authority is viewed as exclusively coercive, freedom as primarily negative, autonomy as automatically possessed, and equality as incompatible with differentiated appraisal of moral achievement and expertise. Stalnaker retrieves early Confucianism as a corrective because it does not present authority and autonomy in competitive terms. Instead, early Confucianism advocates that properly submitting oneself to the right sort of authority and dependent social relationships is the indispensable path for cultivating autonomy. The article lifts up three attractive claims of the proposal and probes the tension between virtue, hierarchy, and cosmology in early Confucianism.